Α-Fe2O3 thin films deposited by a facile spray pyrolysis technique for enhanced ethanol sensing. (1st May 2023) - Abedi, Seyyedeh Parisa; Rahmani, Mohammad Bagher; Rezaii, Farkhondeh
Abstract: In this research, α- Fe2 O3 (hematite) thin films were deposited by spray pyrolysis on glass substrates at various growth temperatures of 350, 400, 450, and 500 °C. Samples were characterized using versatile techniques to study their morphological, structural, and optical properties. X-ray diffraction patterns and Raman spectra confirmed the formation of the hexagonal structure of hematite. Electron microscope images show the growth of cubic nanoparticles on the surface of all synthesized samples, the average size of cubes for the sample with the best sensing performance is about 56.2 nm. Ethanol sensing characteristics of samples were investigated at four elevated temperatures of 175, 200, 225, and 250 °C, exposed to different concentrations of ethanol. The film deposited at the substrate temperature of 350 °C reached the best responses of 30.2% toward 100 ppm and 51.4% toward 1000 ppm of ethanol at the optimum working temperature of 200 °C. The response and recovery times were recorded at 279 and 536 s, respectively, when this sensor was exposed to 100 ppm ethanol vapor at 200 °C. A possible mechanism of ethanol sensing is also discussed. This study optimized the growth conditions and sensing parameters of hematite thin films for ethanol sensing applications.